P285 Rationalising the use of specimen pots following colorectal polypectomy– a small step towards sustainable endoscopy. (19th June 2022) - Yong, Karl King; He, Yun; Cheung, Hoi Ching; Sriskandarajah, Ramya; Jenkins, William; Beg, Sabina
Abstract : Introduction: Endoscopy departments are responsible for the third highest rate of hospital related greenhouse gas (GHG) emissions. In this study, we aim to determine whether combining multiple diminutive colorectal polyps within a single specimen pot can reduce waste without causing deleterious clinical impact. Methods: This was a retrospective observational study of colorectal polyps resected during 2019, within the Imperial College Healthcare Trust. The numbers of pots for polypectomy specimens were calculated and corresponding histology results were extracted. We modelled the potential specimen pot savings if all polyps were sent together and the number of advanced lesions we would not be able to locate if we adopted this strategy. GHG emissions were estimated based on previous study using a Life Cycle Assessment, at 0.28kg CO2 per pot. Results: A total of 11, 781 lower GI endoscopies were performed. There were 5134 polyps removed and 4192 pots used. This equates to 1, 174 kg CO2 released. There were 4568(90%) polyps measuring 0-10mm. 7(0.2%) of these diminutive polyps were cancers and 18(0.4%) with high-grade dysplasia. 2(8%) of these lesions were predicted to have advanced histology at the time of endoscopy. If we combined all diminutive polyps in a single pot, the total pots used would be reduced to 2779. Conclusions: A change in practice by placing diminutive polyps collectively in one pot would have resulted in GHG emission savings equivalent to 438 pounds of coal combustion. The reduction in GHG emissions from judicious use of specimen pots would be amplified with a change in practice on a national level. (1757 characters)